2020
DOI: 10.1089/ast.2020.2216
|View full text |Cite
|
Sign up to set email alerts
|

Cometary Glycolaldehyde as a Source of pre-RNA Molecules

Abstract: Over 200 molecules have been detected in multiple extraterrestrial environments, including glycolaldehyde (C 2 (H 2 O) 2 , GLA), a two-carbon sugar precursor that has been detected in regions of the interstellar medium. Its recent in situ detection on the nucleus of comet 67P/Churyumov-Gerasimenko and through remote observations in the comae of others provides tantalizing evidence that it is common on most (if not all) comets. Impact experiments conducted at the Experimental Impact Laboratory at NASA's Johnson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 169 publications
(235 reference statements)
0
7
0
Order By: Relevance
“…Although current HPT experiments did not provide any positive support for the formation of protein from glycine by astronomical impact events, the formation of protein from other amino acids by HPT processing needs to be investigated in the future. The stability of significant amounts of glycine after the HPT process indicates that comet impacts could basically deliver significant amounts of biomolecules into the early Earth, as suggested in some other studies by high-pressure shock experiments as well 25,26 . As discussed in the previous paragraph, the conversion of glycine to ethanol implies the release of nitrogen-containing molecules and some reactive gases into the system, which are inevitably available to react with other molecules to produce other organic compounds on the Earth.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although current HPT experiments did not provide any positive support for the formation of protein from glycine by astronomical impact events, the formation of protein from other amino acids by HPT processing needs to be investigated in the future. The stability of significant amounts of glycine after the HPT process indicates that comet impacts could basically deliver significant amounts of biomolecules into the early Earth, as suggested in some other studies by high-pressure shock experiments as well 25,26 . As discussed in the previous paragraph, the conversion of glycine to ethanol implies the release of nitrogen-containing molecules and some reactive gases into the system, which are inevitably available to react with other molecules to produce other organic compounds on the Earth.…”
Section: Discussionmentioning
confidence: 53%
“…In this study, we apply the HPT method for the first time to glycine amino acid to have an insight into the survival of amino acids or the formation of protein by astronomical impact events. The findings of this study are of significance for astrobiology because the degree of survival of organic materials during impacts by small solar system bodies is an important issue in understanding the delivery of necessary molecules for life onto the Earth by comets and other small solar system bodies 25,26 . Moreover, the formation mechanism of proteins from amino acids in the early Earth conditions is still a key issue in understanding the origin of life 1,8 .…”
mentioning
confidence: 88%
“…Marchi et al, 2014). Laboratory impact experiments have shown that a significant fraction of the molecules contained in comets and meteorites could have been delivered intact to the early Earth (Pierazzo and Chyba 1999;Bertrand et al, 2009;McCaffrey et al, 2014;Todd and Öberg 2020;Zellner et al, 2020). Once on the planetary surface, under the appropriate physical/chemical conditions, these molecules could have allowed the development of the prebiotic processes that led to the dawn of life on Earth.…”
Section: Conclusion: Implications For the Rna-worldmentioning
confidence: 99%
“…Marchi et al 2014). Laboratory impact experiments have shown that a significant fraction of the molecules contained in comets and meteorites could have been delivered intact to the early Earth (Pierazzo and Chyba 1999;Bertrand et al 2009;McCaffrey et al 2014;Zellner et al 2020;Todd and Öberg 2020). Once on the planetary surface, under the appropriate physical/chemical conditions, these molecules could have allowed the development of the prebiotic processes that led to the dawn of life on Earth.…”
Section: Conclusion: Implications For the Rna-worldmentioning
confidence: 99%